Menata Pendidikan Abad 21: Kurikulum, Guru, dan Tantangan Era Industri 4.0 - Ahmad Nur Kolis (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This article aims to analyze the direction of educational planning in the Industrial Revolution 4.0 era by emphasizing the importance of curriculum adjustment and strengthening teacher competency in facing technological disruption and the demands of the 21st century. The research was conducted with a qualitative approach through a literature study method, using primary and secondary literature covering educational policies, scientific journals, and regulations on the linearity of teacher diplomas. The results of the study indicate that the success of educational planning depends not only on an adaptive curriculum, but also on teacher professionalism and the application of student-centered and community-based learning methods. Technology integration, strengthening digital literacy, and 21st century skills are key components in designing a relevant and competitive education system. Thus, educational planning in the digital era must be flexible, collaborative, and responsive to social change and the needs of the future world of work.